2018
DOI: 10.3390/ijms19103221
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Autophagy Inhibitor Alpha-Hederin Promoted Paclitaxel Cytotoxicity by Increasing Reactive Oxygen Species Accumulation in Non-Small Cell Lung Cancer Cells

Abstract: Chemoresistance is a major limiting factor that impairs the outcome of non-small cell lung cancer (NSCLC) chemotherapy. Paclitaxel (Tax) induces protective autophagy in NSCLC cells, leading to the development of drug resistance. We recently identified a new autophagy inhibitor (alpha-hederin) and hypothesized that it may promote the killing effect of Tax on NSCLC cells. We found that alpha-hederin (α-Hed) could block late autophagic flux in NSCLC cells by altering lysosomal pH and inhibiting lysosomal cathepsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 48 publications
2
29
0
Order By: Relevance
“…Briefly, autophagy is a highly conserved cellular process during evolution, which is induced by diverse pathologies and cellular stresses containing nutrient deprivation, endoplasmic reticulum stress, and hypoxia 17 . Autophagy has also been involved in cancer resistance to multiple chemotherapeutic drugs, including cisplatin 18 , paclitaxel 19 , and gemcitabine 20 . Autophagy plays a vital role in regulating colorectal cancer chemoresistance, blocking of which will be developed as a promising therapy strategy for colorectal cancer treatment 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, autophagy is a highly conserved cellular process during evolution, which is induced by diverse pathologies and cellular stresses containing nutrient deprivation, endoplasmic reticulum stress, and hypoxia 17 . Autophagy has also been involved in cancer resistance to multiple chemotherapeutic drugs, including cisplatin 18 , paclitaxel 19 , and gemcitabine 20 . Autophagy plays a vital role in regulating colorectal cancer chemoresistance, blocking of which will be developed as a promising therapy strategy for colorectal cancer treatment 21 .…”
Section: Introductionmentioning
confidence: 99%
“…More and more evidences has indicated that basal autophagy plays a role of protector against ROS-induced cytotoxicity. 35,36) Our data were consistent with these finding. Therefore, induction of autophagy may exhibit a protective effect against the cytotoxic actions in cancer cells, while inhibition of autophagy enhanced cytotoxicity.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, autophagy inhibitors are expected to assist common chemotherapeutic agents in cancer therapy. 38,39 However, BBR was widely reported to induce autophagy, 10,[15][16][17] and our results confirmed BBR as an autophagy-inducing agent in breast cancer cells (Figure 3). We then asked if the BBR-induced autophagy is responsible for the hormetic effect of BBR.…”
Section: Discussionsupporting
confidence: 80%